Dazzling cool white light emission from Ce3+/Sm3+ activated LBZ glasses for W-LED applications. Issue 17 (1st December 2018) - Vijayalakshmi, L.; Kumar, K. Naveen; Hwang, Pyung
Abstract: We synthesized a batch of co-doped (Ce 3+ +Sm 3+ ): LBZ glass specimens by melt quenching process and their structural and radiation properties were studied by employing XRD, FE-SEM, optical absorption, photoluminescence and lifetime measurements. UV–Vis–NIR absorption studies of the co-doped (Ce 3+ +Sm 3+ ): LBZ glassy matrix displays pertinent bands of both Ce 3+ and Sm 3+ ions. Individually doped Sm 3+ : LBZ glass exhibit bright orange emission at 603 nm ( 4 G5/2 → 6 H7/2 ) under the excitation of 403 nm. Nevertheless, the luminescence intensities pertaining to Sm 3+ were extraordinarily increased by co-doping with Ce 3+ ions to Sm 3+ : LBZ glassy matrices because of energy transfer from Ce 3+ to Sm 3+ . The fluorescence spectra of co-doped (Ce 3+ +Sm 3+ ): LBZ exhibits characteristic emission bands of Ce 3+ (441 nm, blue) and Sm 3+ (603 nm, reddish orange) under the excitation of 362 nm. Decay curves of Ce 3+ and Sm 3+ ions in co-doped glass has been fitted to double exponential nature. The decreasing lifetime of donor ion and rising lifetime of acceptor ion in double doped glass could support the energy transfer from Ce 3+ to Sm 3+ ions in the host matrix. The CIE coordinates and CCT values were calculated for all the obtained co-doped glassy samples from their luminescence spectra. By adding Ce 3+ ions to individually doped Sm 3+ : LBZ glass matrix, the emitting color changes from reddish orange to white light which resembles the energy transfer from Ce 3+ to Sm 3+ ions. These studies, perhaps implied that attained co-doped (Ce 3+ +Sm 3+ ): LBZ glassy samples are potential materials for white lighting appliances.